Respuesta :
Answer:
Simplifying
(9x + -4) + -1(3x + 2) = 0
Reorder the terms:
(-4 + 9x) + -1(3x + 2) = 0
Remove parenthesis around (-4 + 9x)
-4 + 9x + -1(3x + 2) = 0
Reorder the terms:
-4 + 9x + -1(2 + 3x) = 0
-4 + 9x + (2 * -1 + 3x * -1) = 0
-4 + 9x + (-2 + -3x) = 0
Reorder the terms:
-4 + -2 + 9x + -3x = 0
Combine like terms: -4 + -2 = -6
-6 + 9x + -3x = 0
Combine like terms: 9x + -3x = 6x
-6 + 6x = 0
Solving
-6 + 6x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6' to each side of the equation.
-6 + 6 + 6x = 0 + 6
Combine like terms: -6 + 6 = 0
0 + 6x = 0 + 6
6x = 0 + 6
Combine like terms: 0 + 6 = 6
6x = 6
Divide each side by '6'.
x = 1
Simplifying
x = 1
Hope this helped you! :3
Answer:
6x - 10.
Step-by-step explanation:
Remove the parentheses.
Removing the first set does not alter the contents but with the second set of parentheses we need to distribute the negative over the contents'
(9x - 4) - (3x + 2)
= 9x - 4 - 3x - 6
= 6x - 10.